PENGARUH PENGALAMAN KERJA, DISIPLIN KERJA, DAN KEPUASAN KERJA TERHADAP PRESTASI KERJA KARYAWAN SWAKELOLA BALAI BESAR WILAYAH SUNGAI SERAYU OPAK YOGYAKARTA - Inayat Hanum Indriati; Hashfi Amga Nazhifi (Program Studi Akuntansi, 2022)
This study aims to determine the effect of work experience, work discipline and job satisfaction on job performance. This research was conducted at the Serayu River Opak River Basin, Yogyakarta in 2021. This research is a quantitative study with 56 respondents and the sampling technique is simple random sampling technique. Data collection techniques were carried out by means of interviews and questionnaires. The analysis technique used is multiple linear regression analysis.The results showed that partially work experience has a significant positive effect on work performance with a sig value of 0.000 <0.05, work discipline has a significant positive effect on work performance with a sig value of 0.002 <0.05, job satisfaction has a significant positive effect on work performance with a value sig 0,000 <0.05. The results of the study simultaneously work experience, work discipline, and job satisfaction on job satisfaction with a sig value of 0.000 <0.05 and F count of 62.708> 2.779 (F table). The effect of work experience, work discipline and job satisfaction on work performance is indicated by the Adjusted R Square value of 77.1%, the remaining 22.9% is influenced by other variables not examined in this study.